2015
DOI: 10.1161/circinterventions.115.002786
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ex Vivo Autologous and In Vivo Platelet Transfusion in the Reversal of P2Y 12 Inhibition by Clopidogrel, Prasugrel, and Ticagrelor

Abstract: T he addition of P2Y 12 receptor inhibiting drugs to aspirin therapy has resulted in improved clinical outcome secondary to reduced recurrent ischemic events in patients with acute coronary syndromes (ACS) or after percutaneous coronary intervention (PCI).1-3 The ischemic benefit is offset by significant morbidity and mortality associated with major bleeding complications in the both coronary artery bypass graft 4 and the nonoperative setting. 5 Indeed, the clinical benefit of systematic pretreatment with P2Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 18 publications
(27 reference statements)
6
59
0
2
Order By: Relevance
“…This is in line with results from previous studies, which showed no effect or only a minor effect of platelet transfusion on ADP‐induced aggregation8, 9, 10 and an improvement in AA‐induced aggregation8 in patients treated with ASA and ticagrelor. Platelet transfusions may therefore still be of clinical importance in patients with ongoing DAPT, as they markedly increase AA‐induced aggregation and can therefore treat the platelet inhibition induced by ASA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with results from previous studies, which showed no effect or only a minor effect of platelet transfusion on ADP‐induced aggregation8, 9, 10 and an improvement in AA‐induced aggregation8 in patients treated with ASA and ticagrelor. Platelet transfusions may therefore still be of clinical importance in patients with ongoing DAPT, as they markedly increase AA‐induced aggregation and can therefore treat the platelet inhibition induced by ASA.…”
Section: Discussionsupporting
confidence: 92%
“…In patients on ticagrelor, platelet transfusion has little or no effect,8, 9, 10 and there is no currently available antidote to ticagrelor. New alternatives are therefore needed to reduce the risk of excessive bleeding in ticagrelor‐treated patients who have ongoing bleeding or who are in need of emergent surgery.…”
Section: Introductionmentioning
confidence: 99%
“…If bleeding occurs during surgery, platelet transfusion has been shown to effectively counteract ASA effects. [166][167][168] This finding further supports the possibility of continuing ASA throughout the perisurgical period as ASA allows direct antiplatelet effect reversal if clinically indicated. The increased risk of bleeding complications if ASA and other antithrombotic drugs are not discontinued should be weighed against the potentially increased risk of thrombotic complications during the pre-operative cessation period.…”
Section: 157supporting
confidence: 55%
“…5 However, in interpreting the data, some issues and important aspects merit mentioning: First, in APTITUDE, various platelet function profiles were used as surrogate end points to assess the pharmacological characteristics of the currently available oral P2Y 12 receptor inhibitors in a setting of platelet transfusion for platelet function restoration. Although platelet function markers for this study were wisely chosen, the interplay of blood platelets, various signaling cascades, and the entire coagulation system to achieve hemostasis is complex and can hardly be explored entirely by ex vivo testing.…”
Section: See Article By O'connor Et Almentioning
confidence: 99%
“…As long as this is not the case, we have to take the data coming from (in vitro) studies such as APTITUDE 5 and others [6][7][8][9][10] as the best available evidence for guidance of patient treatment. Second, the comparatively low sample size for prasugrel-treated patients (n=6) and ticagrelor-treated patients (n=3) in the APTITUDE-CABG cohort precludes from drawing definite conclusions on the feasibility of immediate and sustained platelet restoration after platelet transfusion with these 2 agents.…”
Section: Sibbing and Massberg Restoring Platelet Function On Antiplatmentioning
confidence: 99%